Cross-Border Dialogues: A Collaborative Instructional Design Inquiry to Promote Equity and Diversity - Zhang, Zheng; Lee, Icy; Chan, Helen Wan Yu; Guo, Qi; Kuan, Angela; Lee, Jessica Sum Laam; Ma, Qianhui; Ng, Natalie Ching Tung; Trad, Rozan (Education sciences, 2023)
The COVID-19 pandemic complicates ingrained educational inequalities around the globe and foregrounds the pertaining challenges that teachers have encountered due to school closures and the shift to distance learning. This cross-border teacher education project intended to examine how academics and pre-service teachers in different geographic locales could collaboratively explore equitable learning opportunities for diverse learners through the use of critical media literacies to respond to interconnected global crises. In this six-week cross-border teacher education project, we recruited four Mandarin and English literacy teacher candidates in Hong Kong to interact with one another and one Canadian professor as part of the teacher preparation phase of a larger-scale cross-border research project that connects youth from Hong Kong and Canada in a social networking space. For the purposes of teacher professional development, the Hong Kong teacher candidates and Canadian researchers engaged in collective exploration of how instructional designs in literacy education could promote equitable learning opportunities for diverse learners. Findings show that the cross-border teacher education project supported teacher candidates’ development of pedagogical skills and espoused their agency in promoting educational equity and collective problem-solving through critical media literacies. Findings relate the teacher candidates’ shifted perspectives from focusing on students’ decontextualized language skills to nurturing critical media skills. Changing from a deficit-oriented view about what literacy learners could not do, the teacher candidates also adopted an asset-oriented view about the linguistic and cultural repertoires that diverse learners could bring to literacy classrooms.